Sistema GH/IGF-I nas características metabólicas e atividade reprodutiva pós-parto em bovinos - Schneider, Augusto (2011)
Fertility in cattle is highly influenced by metabolic hormones. Of special interest for the reproductive axis are growth hormone (GH) and insulin-like growth factor (IGF-I). The aim of this thesis were 1) to characterize liver GHR and IGF-I expression in postpartum lactating beef cows and its relation to first ovulation; 2) to characterize GHR and IGF-I expression in granulosa and luteal cells; 3) to determine the effect of prepartum somatotropin on the postpartum resumption of ovarian activity; and 4) to determine the effect of the GHR AluI polymorphism on the fertility of Holstein cows. The expression of GHR and IGF-I mRNA in the liver of postpartum lactating beef cows was not different between ovulatory and non-ovulatory cows, as well as it not change from 0 to 40 days postpartum. These data indicated that beef cows did not go through the same pattern of dissociation of the GH/IGF-I as observed for dairy cattle. Regarding the characterization of GHR and IGF-I expression in luteal and granulosa cells, it was possible to observe that GHR, IGF-I and SOCS expression were clearly higher in luteal than granulosa cells, but not different between atretic and estrogen active follicles. Moreover, GHR and IGF-I expression were not correlated in granulosa and luteal cells. With these results, we choose to focus on strategies in dairy cattle and not based on local regulation of GHR/IGF-I. In this sense, the use of prepartum somatotropin was benefitial in antecipate the resumption of postpartum ovarian activity. Further, treated cows had increased milk production and decreased concentrations of NEFA in the early postpartum. Also, the strategy based on the genotyping of Holstein cows for the GHR AluI polymorphism indicated that cows carrying the AluI(-/-) genotype had lower milk production and shorter calving conception interval. Cows carrying at least one AluI(-) allele also had a shorter calving conception interval and less number of AI per conception. This way, it is clear the importance of the GH/IGF-I system to the reproductive and productive performance of postpartum dairy cows. More studies, with new strategies or combining different strategies can bring even more benefits to the production systems.